An Evaluation of the Implementation of Merdeka Curriculum Policy in English Lesson - Aprilia, Disti; Izdihara, Salsabila Izdihara Salsabila; Apoko, Tri Wintolo (Universitas Muhammadiyah Gresik, 2024)
Merdeka Curriculum is a curriculum substituting the previous national curriculum known as Curriculum 2013, and has been widely used in schools since 2022. This curriculum is believed to contribute the quality of education in Indonesia, mainly for English teachers. Thus, this study examines the implementation of the Merdeka Curriculum policy in English lesson in Indonesian secondary schools. The study used a qualitative descriptive approach, concentrating on the teaching strategy, teaching and learning process, and assessment methods used. The context and the participant of this study is two English teachers at one of state senior high schools in Jakarta, Indonesia. The findings show that teachers have created instructional modules that include a variety of learning mediums and methodologies, with a preference for digital media. Multiple-choice quizzes, essays, and projects are used to assess learning, which aligns with the curriculum’s focus on critical thinking, creativity, and problem-solving skills. The study emphasizes the need for a comprehensive approach to ensuring the Merdeka Curriculum’s successful implementation.